2011
DOI: 10.1097/bot.0b013e3181e5e160
|View full text |Cite
|
Sign up to set email alerts
|

Bone Transport for Postinfectious Segmental Tibial Bone Defects With a Combined Ilizarov/Taylor Spatial Frame Technique

Abstract: All patients achieved complete union and eradication of infection. The results were evaluated according to Association for the Study of the Method of Ilizarov criteria: 83% were excellent and 17% were good in terms of bony outcomes; functional results were excellent in 50%, good in 42%, and fair in 8%. Combined Ilizarov/TSF trifocal and bifocal techniques for the treatment of segmental tibial bone defects achieve union without malalignment of the mechanical axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 18 publications
3
87
0
Order By: Relevance
“…The Ilizarov method for the treatment of tibial non-unions associated with bone defects generally involves bifocal or trifocal osteosynthesis [1,34] , compressing bone at one level to achieve union while simultaneously applying distraction to the same bone at another level to regenerate bone mass. These Ilizarov methods of limb salvage include both bone transport [1,4,5,7,[9][10][11][12]34,[36][37][38][39][40][41][42][43] and acute shortening/lengthening [5,[7][8][9]36,[44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…The Ilizarov method for the treatment of tibial non-unions associated with bone defects generally involves bifocal or trifocal osteosynthesis [1,34] , compressing bone at one level to achieve union while simultaneously applying distraction to the same bone at another level to regenerate bone mass. These Ilizarov methods of limb salvage include both bone transport [1,4,5,7,[9][10][11][12]34,[36][37][38][39][40][41][42][43] and acute shortening/lengthening [5,[7][8][9]36,[44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…Wide resection of bone is frequently required during Ilizarov transport techniques [1,2,16,21], leaving the surgeon facing a difficult problem. The remaining gap reduces progressively during transport, but in the interim, the repair process is shifted from a normal biological fracture response to a process in which a fibrocartilaginous tissue caps the bone, mimicking nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Ilizarov approach consisted of simple compression of these tissues after bone transport was complete, and this was eventually associated with periods of distraction to stimulate osteogenesis [3,9,12,22,23]. More recently, however, some groups have expressed concern about the healing potential of this technique, proposing osteotomy of the docking ends and removal of the interposing tissue as a solution [6,13,19,21]. With this technique, a biological environment more like fracture healing is restored and consolidation is considered more predictable.…”
Section: Introductionmentioning
confidence: 99%
“…Sala et al [6] reported that in their study group consisting of 12 cases, docking-side revision with autogenous bone grafting was necessary in 83% of cases. Lowenberg et al [15] reported a rate of 8.8% for docking-side nonunion even though they performed autogenous bone grafting at the docking side.…”
Section: Discussionmentioning
confidence: 98%
“…During this period, the patient was closely monitored to avoid any circulation problems. On day 15 after the osteotomy, [6] lengthening was started from the osteotomy regions at 3x0.25 mm/day (total 1.5 mm/day) for the bifocal bone transport, and the patient was discharged as an outpatient with polyclinic follow-up.…”
Section: Case Reportmentioning
confidence: 99%